Biventricular diastolic function assessed by Doppler echocardiogram in children vertically infected with human immunodeficiency virus - Mauricio L. Silva; Silvia M. Nassar; André P. Silva; Leandro L. Ponce; Maria M. de S. Pires (Elsevier, 2014)
Objective: to determine, by Doppler-echocardiography, the frequency of cardiac diastolic dysfunction in asymptomatic and clinically stable pediatric patients with vertical infection by the human immunodeficiency virus (HIV), from the cardiovascular viewpoint. Methods: this was an observational, prospective, and cross-sectional study, performed at a regional referral clinic for patients with HIV, in a convenience sample of 94 individuals, assessing biventricular diastolic function by Doppler-echocardiography, and weight, blood hemoglobin, and percentage of lymphocytes T-CD4+. Results: fifty patients had diastolic dysfunction. Left ventricular dysfunction occurred in 38.7%, and the predominant type of dysfunction was decreased myocardial compliance. Right ventricular dysfunction was observed in 29.4% of the sample, and abnormal relaxation was the most prevalent type. Simultaneous biventricular dysfunction occurred in 14.1% of the individuals. There was no association between dysfunction and the immune status. Conclusions: diastolic dysfunction occurred, individually or simultaneously, with no association with immune status; decreased myocardial compliance was predominant in the left ventricle, and abnormal relaxation in the right ventricle. Resumo: Objetivo: verificar, por meio do ecocardiograma com Doppler, a frequência de disfunção cardíaca diastólica em pacientes com infecção vertical pelo vírus da imunodeficiência humana na faixa pediátrica, assintomáticos e clinicamente estáveis do ponto de vista cardiovascular. Métodos: estudo observacional, prospectivo e transversal, realizado em um Ambulatório de Referência Regional para pacientes portadores do vírus da imunodeficiência humana, com uma amostra de conveniência de 94 pacientes, avaliados pelo sexo, idade, peso, função diastólica biventricular ao Doppler, hemoglobina sanguínea e percentual de linfócitos T-CD4+. Resultados: apresentaram disfunção diastólica 50 pacientes. Disfunção ventricular esquerda ocorreu em 38,7% deles, e o tipo de disfunção predominante foi diminuição da complacência miocárdica. A disfunção ventricular direita foi evidenciada em 29,4% da amostra, sendo o tipo relaxamento anormal o mais prevalente. Disfunção biventricular simultânea ocorreu em 14,1% dos indivíduos. Não houve associação da disfunção com o estado imunológico. Conclusões: foi verificada disfunção diastólica, isolada ou simultânea, sem associação com o estado imunológico, sendo a diminuição da complacência miocárdica mais comum no ventrículo esquerdo e relaxamento anormal no ventrículo direito. Keywords: Ventricular function, Infectious diseases, Children, Palavras-chave: Função ventricular, Doenças infecciosas, Crianças